Registro y Control de Inventario del “GAD PARROQUIAL” Ricaurte - Cevallos Cedeño, Genesis Ariana (2018)
In the Society in general, people have been in need of control of the things they possess in order to know correctly what their heritage is, inside of the companies the same parameter has been applied to define the properties of the same, it is for this reason it has been considered to formulate a scheme that helps with this medium. It is for this reason that the present work focuses on the need to carry a correct control of the inventory with which the institution has, which allows to know in a concrete and exact, the assets that are owned by the institution, and that remain in it during a certain period of time. For this purpose, the line of Financial Management and Social Commitment research that the company must maintain organization in front of the community. This research was carried out in the Autonomous Decentralized Parochial Government of Ricaurte, which is a legal institution that was created under the Code regime Organic Territorial Organization Autonomy and Decentralization (COOTAD), which allows the rural sectors of the cantons of our country to have an organization legal assistance to obtain benefits for the territory, such as the works that They need the citizens. During the investigative process of this case study we have taken as reference Respect for the Laws, Regulations and Regulations that have been created for the correct functioning of the Public Sector Institutions, the techniques used in the study of case is through interview and observation, in addition to the use of research methodology descriptive as a mechanism for presenting information.